2012
DOI: 10.1097/bpo.0b013e318255b17b
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Displaced Supracondylar Humerus Fractures

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 14 publications
1
71
0
10
Order By: Relevance
“…The pooled result of iatrogenic ulnar nerve injury in the current study is in agreement with previous reviews [1,3,5,38,40,52]. Babal et al [3] performed a meta-analysis which was derived almost exclusively from retrospective studies and concluded that the medial pin carried the greater overall risk of nerve injury as compared with a lateral-pin-only construct, and that the ulnar nerve was at risk of injury in patients who had medial pins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pooled result of iatrogenic ulnar nerve injury in the current study is in agreement with previous reviews [1,3,5,38,40,52]. Babal et al [3] performed a meta-analysis which was derived almost exclusively from retrospective studies and concluded that the medial pin carried the greater overall risk of nerve injury as compared with a lateral-pin-only construct, and that the ulnar nerve was at risk of injury in patients who had medial pins.…”
Section: Discussionsupporting
confidence: 91%
“…Pin tract infection, superficial infection, reoperation, and compartment syndrome also were compared. Previous systematic reviews were aimed mainly at iatrogenic nerve injury, deformity, or loss of reduction [3,5,29,38,52]. Few meta-analyses or systematic reviews compared the postoperative functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous pinning is a popular method of choice for supracondylar fractures [6][7][8] and has been reported to be a safe and cost-effective method that provides good functional results [7][8][9][10]. Even dislocated supracondylar fractures can be treated by repositioning and casting with an excellent functional outcome [11].…”
Section: Introductionmentioning
confidence: 99%
“…5 The optimal pin configuration for displaced supracondylar fractures in children remains controversial. 6 This study evaluated the outcome after closed reduction and pinning using a Kirschner wire inserted laterally and another inserted vertically through the olecranon for displaced supracondylar humeral fractures.…”
mentioning
confidence: 99%